(untitled) (Economic studies journal, 2021)
Abstract: This study aimed to identify the impact of good governance on the ethics of administrative work in Commercial banks operating within the municipality of Haryana. The study used the descriptive and analytical method, and to achieve the objectives of this study, a questionnaire was prepared and distributed that aimed to test hypotheses. Number (106) questionnaire on the sample of the study, and (84) questionnaires were retrieved, Meaning a percentage of (79). the most important findings of the study is the existence of an impact of good governance (governance) in its dimensions (participation, accountability, transparency, justice and equality) combined in strengthening the ethics of management in commercial banks in the municipality of Haryana, and one of the most important recommendations of the study is to pay attention to the concepts of good governance of commercial banks. And the application of the code of work ethics for banking and the development of a governance Guide for Libyan banks to be supportive of laws related to banking in Libya.